Analisis Perencanaan Biaya Konstruksi Jalan Rigid Pevement Ruas Jalan Poros Singki’ Alang-Alang Kab.Toraja Utara - Pago, Marthen; Badrun, Burhanuddin; Yunus, Ahmad Yauri (Program Studi Teknik Sipil Universitas Bosowa, 2023)
The purpose of this study is to know the costs needed for rigid pavement construction, and to find out the capacity of the road How much Singki – Alang-alang road capacity according to The Bina Marga Rigid Pavement Planning 2017. Calculation of construction costs based on data from the Bina Marga Office of South Sulawesi Province in the form of work volume, unit price analysis and plan drawings. From hasi cost analysis shows that rigid pavement construction costs Rp 7,295,591,000.-.